2018
DOI: 10.1371/journal.pone.0205065
|View full text |Cite
|
Sign up to set email alerts
|

Tropheryma whipplei colonization in HIV-infected individuals is not associated with lung function or inflammation

Abstract: Studies demonstrate that Tropheryma whipplei (T. whipplei) is present in the lungs of healthy individuals without acute respiratory symptoms or acute respiratory infection and is more common in the lungs of HIV-infected individuals and in smokers. The impact of T. whipplei colonization in the lung on local inflammation and pulmonary dysfunction in HIV-infected individuals is currently unknown. In this study, we performed specific polymerase chain reaction (PCR) and sequencing for T. whipplei in bronchoalveolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…In addition to this, markers of immune activation were found to be decreased in T. whipplei carriers in our cohort. This finding is in agreement with a study on T. whipplei colonization of the lung in PLHIV, where T. whipplei positivity was not associated with increased systemic or local inflammation [ 14 ]. Indeed, Moos and Schneider related an absence of an inflammatory response against T. whipplei to the establishment of a chronic infection, which might in part explain the higher prevalence in individuals receiving anti-inflammatory antiretroviral therapy [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition to this, markers of immune activation were found to be decreased in T. whipplei carriers in our cohort. This finding is in agreement with a study on T. whipplei colonization of the lung in PLHIV, where T. whipplei positivity was not associated with increased systemic or local inflammation [ 14 ]. Indeed, Moos and Schneider related an absence of an inflammatory response against T. whipplei to the establishment of a chronic infection, which might in part explain the higher prevalence in individuals receiving anti-inflammatory antiretroviral therapy [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with a study on PLHIV in Europe, there was no accumulation of acute or chronic symptoms in subjects carrying T. whipplei in our cohort from Sub-Saharan Africa [ 15 ]. Likewise, Qin et al reported no impairment of pulmonary function in PLHIV with T. whipplei positive bronchoalveolar lavage samples [ 14 ]. Our findings are also in line with a recent work from Ghana in which T. whipplei was found equally in symptomatic pediatric cases and controls [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BAL and mouths of 82 HIV-positive and 77 HIV-negative subjects qPCR Higher prevalence and relative abundance of TW in BAL in HIV-positive individuals [13] BAL and induced sputum samples in 76 HIV-infected participants PCR and sequencing Frequency of TW in either BAL or IS was 43.4% [22] bronchial biopsy specimens of a man with a history of intermittent fever and arthritis…”
Section: Methods Comments Referencesmentioning
confidence: 99%
“…It has been associated with smoking and its prevalence decreases with initiation of ART. Despite its presence in the lung, it has not been associated with pulmonary inflammation or lung function (21). The discordance between its high abundance in raw samples and relatively lower abundance in IgG-bound samples could suggest that the absence of an inflammatory response to Tropheryma in the lungs may be due to a lack of active host recognition and response (20,21).…”
Section: Discussionmentioning
confidence: 99%